The roles of T cells in psoriasis - Zhang, Peng; Su, Yuwen; Li, Siying; Chen, Hui; Wu, Ruifang; Wu, Haijing (Frontiers in Immunology, 2023)
Psoriasis is a recurring inflammatory skin condition characterized by scaly, red patches on the skin. It affects approximately 3% of the US population and is associated with histological changes such as epidermal hyperplasia, increased blood vessel proliferation, and infiltration of leukocytes into the skin’s dermis. T cells, which are classified into various subtypes, have been found to play significant roles in immune-mediated diseases, particularly psoriasis. This paper provides a review of the different T lymphocyte subtypes and their functions in psoriasis, as well as an overview of targeted therapies for treating psoriasis.